Design and Synthesis of Thiourea-Conjugating Organic Arsenic D-Glucose with Anticancer Activities - Boqiao Fu; Wenxuan Liu; Yufeng Wang; Guorui Li; Yingsha Wang; Xinyuan Huang; Hongan Shi; Caiqin Qin (Molecules, 2024)
Organic arsenic compounds such as p-aminophenylarsine oxide (p-APAO) are easier for structural optimization to improve drug-like properties such as pharmacokinetic properties, therapeutic efficacy, and target selectivity. In order to strengthen the selectivity of 4-(1,3,2-dithiarsinan-2-yl) aniline 7 to tumor cell, a thiourea moiety was used to strengthen the anticancer activity. To avoid forming a mixture of α/β anomers, the strategy of 2-acetyl’s neighboring group participation was used to lock the configuration of 2,3,4,6-tetra-O-acetyl-β-d-glucopyranosyl isothiocyanate from 2,3,4,6-tetra-O-acetyl-α-d-glucopyranosyl bromide. 1-(4-(1,3,2-dithiarsinan-2-yl) aniline)-2-N-(2,3,4,6-tetra-O-acetyl-β-d-glucopyranos-1-yl)-thiourea 2 can increase the selectivity of human colon cancer cells HCT-116 (0.82 ± 0.06 μM vs. 1.82 ± 0.07 μM) to human embryonic kidney 293T cells (1.38 ± 0.01 μM vs. 1.22 ± 0.06 μM) from 0.67 to 1.68, suggesting a feasible approach to improve the therapeutic index of arsenic-containing compounds as chemotherapeutic agents.